Synergistic effects of serum albumin and HDL cholesterol concentrations on serum oxidized LDL cholesterol concentration in obese individuals with normal glycoregulation and patients with type 2 diabetes mellitus - Pejin Radoslav; Milankov Andrijana; Ičin Tijana; Bajkin Ivana; Niković Jelena; Jovanović Aleksandar; Tanackov Ilija (Vojnosanitetski Pregled)
Background/Aim. Serum albumin and high-density lipoprotein (HDL) cholesterol molecules have multiple physiological functions, including an antioxidant role in neutralizing the harmful effects of oxidized low-density lipoprotein (oxLDL). In obese individuals, albumin and HDL cholesterol molecules are unable to counteract the unfavorable effects of oxLDL cholesterol adequately. The aim of the study was to examine the functional relationships between oxLDL cholesterol, HDL cholesterol, and serum albumin. Methods. The study included 30 obese individuals with newly diagnosed type 2 diabetes mellitus (before and after a three-month treatment with metformin), 30 obese individuals with normal glucose tolerance, and 30 normal-weight subjects (control group). The groups were age- and sex-matched. Results. Both qualitative and quantitative changes in the levels of HDL cholesterol and albumin were detected among the groups. Statistically significant changes were found in the linear correlations between albumin and ox- LDL cholesterol among the study groups. Furthermore, by forming a synergistic influence of independent variables (HDL cholesterol and albumin), expressed through a complex polynomial of the dependent variable (oxLDL) of the quadratic type, statistically significant qualitative and quantitative changes in maximal oxLDL values were observed in all examined groups. Conclusion. The results of our study indicate a potential synergistic effect of albumin and HDL cholesterol in the prevention of oxidative damage, as well as a possible alteration in the quality of the ratio of these parameters in relation to oxLDL cholesterol molecules under conditions characterized by increased oxidative stress.